Legal responsibility for violation of environmental regulations on the land of the Ukrainian Cossacks - Sehorebra, Tetiana (Actual problems of law (Aktual'ni problemi pravoznavstva), 2022)
The article considers penalties for offenses related to natural objects in the Hetman's universals, Kosh’s warrants and in the ancient monument «Rights of the Little Russian People» in 1743. It is shown that the Hetman’s universals differed in the absence of clearly established norms punishments, signs of crimes and allowed a broad interpretation of this category. As measures of legal responsibility, the Zaporozhian Cossacks used penalties and such measures as the cessation of use of natural objects and its transfer to another tenant. The «Rights of the Little Russian People» of 1743 used penalties for offenses related to the destruction of animals, trees, bees, birds, haymaking, illegal fishing and proved their higher size compared to the GDL Statutes of 1588.Based on the results of the research, conclusions are drawn.1. The legal responsibility established by the Hetman's universals was of an uncertain nature, there were no clear penalties for sanctions, which allowed for a broad interpretation of penalties for offenses related to natural objects.2. According to the Orders issued by Zaporizhzhya Kosh, the rules of liability were established in the form of the need to pay a fine and confiscate natural objects from tenants and transfer them to others.3. Penalties recorded in the "Rights of the Little Russian People" of 1743 were systematic, clear in nature and were aimed at protecting certain species of animals, birds, bees, tree trees, haymaking. A comparative analysis of the penalties of Prav 17 1743 and the Statute of the Grand Duchy of Lithuania of 1588 showed higher values of fines in Prava у compared to the Lithuanian Statute.